John Henry - Lester, Julius; Pinkney, Jerry (New York, 1994)
Retells the life of the legendary African American hero who raced against a steam drill to cut through a mountain.
Keywords: John Henry (Legendary character); Legends; John Henry (Legendary character); Folklore, Afro-American; Folklore; United States